Transcultural health: attitudes, perceptions, knowledge of Italian nurses. An observational study - Vitale, Elsa; Lupo, Roberto; Calabrò, Antonino; Ilari, Federica; Lezzi, Alessia; Zacchino, Simone; Vergori, Sergio; Chetta, Giorgia; Latina, Salvatore; Benedetto, Angelo; Lezzi, Pierluigi; Conte, Luana (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. The Italian health profile of foreigners depends from several factors and events, such as: environmental, microbiological, cultural and / or behavioral. Healthcare professionals might to have greater and better basic and post-basic training in approaching foreign users. Listening and empathy, with complementary training can help to reduce distances and better understand the patient’s socio-cultural background. The aim of the study is to explore the basic intercultural knowledge of the Italian nurses, the perception of the problems encountered during the interaction with foreign users and any solution strategies. Methods. From December 2020 to March 2021 a national observational study was conducted by involving 327 nurses. Results. 85.5% among participants were females and most of them aged between 20 and 30 years (20.20%) and were employed in medical wards (22.60%). Among the hindering barriers explored, linguistic ones are highlighted (41.30%), specifically for the description of hospital rules (34.90%) and of social and health regulations (34.90%). Conclusions. From the present findings, it emerges that the cultural competence of nurses could be developed by offering a multicultural education through basic and post-basic courses. (www.actabiomedica.it)